Trichoderma viride a Mycoparasite for the Control of Phytophthora cinnamomi - Karthikeyan, A.; Kumar, Shailendra; Kumar, Surinder (Indian Forester, 2003)
A laboratory experiment was condncted to study the biocontrol effect of Trichoderma viride on Phytophthora cinnamomi. Simultaneously, the chemical treatments like carbendazim and Zn dust individually and in combinations were applied on P. cinnamomi. In this experiment, T. viride suppressed the growth of P. cinnamomi and zoosporangial development more effectively than other chemical treatments. It is, therefore, concluded that applying T. viride against P. cinnamomi might be an eco-friendly method for controlling the disease.